PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP TURNOVER INTENTION MELALUI STRES KERJA SEBAGAI VARIABEL MODERASI - Hartono, Sri; Yakin, Ikram; Rosyid, Bahrur; Fatkhulloh, Amal; Citra, Auliya (JURNAL LENTERA BISNIS, 2025)
This study aims to determine and analyze the influence of the work environment and workload on turnover intention through work stress as a moderating variable. This study is included in the causal research category using a quantitative approach. Sampling using the Slovin Formula totaling 53 employees from a population of 113 people. Data collection techniques were carried out through observation, interviews, and distributing questionnaires. This study analyzed using the help of Smart PLS (Partial Least Square) software version 3.0 to test the strength of the relationship between turnover intention and its independent variables, namely the work environment, workload, and work stress as a moderating variable. The results of this study are the work environment has a significant effect on turnover intention. Workload does not have a significant effect on turnover intention. Work stress is not able to moderate the influence of the work environment and workload on turnover intention.